TRAUMA HEALING DENGAN PELATIHAN REGULASI EMOSI DAN TAFAKUR UNTUK MENINGKATKAN KESEJAHTERAAN SUBJEKTIF - DWI WIDARNA LITA PUTRI (Universitas Islam Negeri Mataram, 2021)
This study aims to determine the effect of emotional regulation training and meditation on improving the subjective well-being of adolescent victims of the Lombok earthquake. The subjects in this study were 26 youth victims of the Lombok earthquake. The hypothesis proposed in this study is that there is a difference in the subjective well-being of earthquake victims who attended training on emotion regulation and meditation with earthquake victims who did not take emotional regulation and meditation training. The research design used is the control group design. Quantitative analysis used an independent sample t-test to determine whether or not there was an effect of emotional regulation training and meditation on improving subjective well-being in the experimental group that was given training on emotion regulation and meditation and the control group who was not given emotional regulation and meditation training. The results of the study, in the form of all aspects of subjective well-being, showed a very significant difference, earthquake victims in the control group and the experimental group were given treatment with a subjective welfare final test score in the form of life satisfaction with a value of p=0.003 (P<0.01) positive affect with a value of p=0.003 (P<0.01) and negative affect with a value of P=0.003 (P<0.01).